Study on the integrated teaching of English education, mental health and students' wellbeing - Zhao, Qian; Shang, Hang (Frontiers in Psychiatry, 2022)
Teachers' attitudes, behavior, and practices play an integral role in enhancing the students’ learning activities. Teachers' strategies ensure the individuals’ professional development by creating a healthy learning environment. The study's primary objective is to analyze students’ attitudes towards learning English as a foreign language. The data was collected from the 359 colleges and universities students by adopting a convenient sampling technique. The study shows English self-concept and teacher behaviour student orientation significantly positively impact attitudes toward learning English as a foreign language. Motivation for English and English Intentions mediate the relationship between English Self-concept, teacher behavior-student orientation, and Attitude toward learning English as a Foreign Language. The study motivates future studies to focus on the EFL, individuals’ learning motivation and intentions in other domains across diverse contexts.